Interpretación de imágenes de satélite con técnicas de machine learning para el monitoreo de cultivos (2020)
Currently is generated a plethora of information useful for several areas of interest. However, a big amount of data requires a considerable increase in effort to be analyzed. Consequently, is proposed the development of an applicative to automaticly interpret the spectral bands of satelital images using machine learning techniques and accurately classify these images.